Financing sustainable agriculture under climate change with a specific focus on foreign aid - Jikun Huang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Agricultural development is facing great challenges in meeting global food security and is expected to face even greater difficulties under climate change. The overall goal of this paper is to examine how foreign aid in particular can be used to achieve the joint objectives of development, mitigation of and adaptation to climate change in agriculture in the developing world. The results show that agriculture is underinvested and foreign aid has not increased sufficiently to assist developing countries achieve sustainable agriculture; substantial funds are needed to finance the wide range of measures for mitigating and adapting to climate change. The paper attempts to examine the successful cases where agricultural mitigation of and adaption to climate change have worked in the developing countries. In this respect, we pose four main questions: What works? What could work? What can be scaled? And what can be transferred?
Keywords: F35; G32; H87; Q54; 330; climate change; finance; foreign aid; agriculture; mitigation; adaption; Landwirtschaft; Landwirtschaftliche Entwicklung; Klimawandel; Ökologischer Landbau; Entwicklungshilfe; Entwicklungsländer